Psychoprophylaxis Of Depressive Situations In Crisis Situations (Eurasian Journal of Learning and Academic Teaching, 2023)
One of today's urgent problems is to study in depth the disorders in various areas that arise in the individual in crisis situations, to develop and implement preventive measures.